Value of Myoglobin, Troponin T and CK-MB in the Early Diagnosis of Acute Myocardial Infarction - Aksoy, Yemliha; Ergin, Ali; Sözüer, M. Erdoğan; İkizceli, İbrahim; Avşaroğulları, Levent; Yıldırım, Cuma (Fırat University, 2006)
Objectives: Substantial portion of patients with chest pain, who arrive to the emergency department, are diagnosed as acute coronary syndrome. Early diagnosis and timely administration of trombolytic agents decrease mortality and morbidity, shorten stay period of the patients at the hospital, and affect prognosis of the disease positively. In the patients with atypical chest pain and nondiagnostic ECG's, markers which are highly sensitive and exclusive in early period are needed for early and accurate diagnosis of AMI. We compared myoglobin and troponin T with CK-MB that is used routinely in the practice to determine their early ruling out and ruling in of AMI. Materials and Methods: Sixty two patients with chest pain presenting to the emergency department were included in the study. Of the patients (n=62) 30 had diagnosis of MI. The remaining 32 patients had diagnosis of UA and nonspesific chest pain. The patients whose clinical conditions may cause false-positive results of marker assays were excluded from the study. At the 2nd, 3th, 4th, 5th, 6th and 12th hours of begining the ches pain, blood were taken for myoglobin, troponin and CK-MB analyses. Results: Sensitivities of myoglobin, troponin T, and CK-MB were 53%, 3%, and 0% respectively. At the same time their NPD's were 68 %, 52 %, and 51 % respectively. In the 5th hour after the onset of chest pain the sensitivities were 100 %, 93 %, and 76 % respectively. In the same time the NPD's were 100 %, 94 %, and 81 %. As a result, myoglobin was found out to be the most sensitive and exclusive marker in early period for diagnosis of AMI. Troponin T was determined as a later sensitive and exclusive marker in diagnosis of AMI. Conclusion: It can be concluded that additional use of CK-MB concurrent measurement of myoglobin, a cardiosensitive marker, and troponin T, a cardiospesific marker, in blood may be an appropriate strategy for early diagnosis of AMI.©2006, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Acil servise göğüs ağrısı şikayeti ile başvuran hastaların önemli bir kısmı Akut Koroner Sendrom tanısı almaktadır. Bu tanının erken konulması ve trombolitik tedavinin veya girişimsel işlemlerin zamanında yapılmasıyla mortalite ve morbidite olumlu yönde etkilenmekte, hastaların hastanede kalış süresi azalıp hastalığın prognozunda iyileşme olmaktadır. Atipik göğüs ağnsı ve nondiagnostik EKG'si olan hastalarda erken AMI teşhisi için erken belirleyici ve dışlayıcı kaabiliyeti yüksek markerlere ihtiyaç vardır. Gereç ve Yöntem: AMI'ı erken tesbit edebilme ve dışlama kaabiliyetlerini belirlemek için miyoglobin ve troponin T'yi rutin olarak kullanılan CKMB ile karşılaştırdık. Çalışmaya 62 göğüs ağrılı hasta alındı. Bunların 30'u AMI tanısı konuldu. Geriye kalan 32 hasta ise UA ve diğer göğüs ağrıları tanısını aldı. Hastalar markerlerin yanlış pozitif oluşturabileceği durumlardan dışlanarak çalışmaya dahil edildiler. Tüm hastalardan ağrının 2, 3, 4, 5, 6 ve 12. saatlerinde myoglobin, troponin ve CK-MB ölçümleri için kan örnekleri alındı. Bulgular: Ağrının 2. saatinde miyoglobin, CK-MB ve troponin T'nin sensitiviteleri sırasıyle %53,%3 ve %0 bulundu. Aynı saatteki negatif prediktif değerleri ise sırasıyla %68 ,%52 ve %51 bulundu. Beşinci saatteki sensitiviteleri ise sırasıyla %100, %93 ve %76 idi. Aynı saatteki NPD'leri ise sırasıyle %100 , %94 ve %81 idi. Çalışmada erken dönemde AMI'ya en duyarlı ve AMI'yı dışlama kaabiliyeti en yüksek marker olarak miyoglobin bulundu. Troponin T ise daha geç belirleyici marker olarak bulundu. Sonuç: Acil serviste AMI'ın erken teşhisinde CK-MB'ye ilaveten kardiyosensitif marker olan miyoglobin ile kardiospesifık marker olan troponin T'nin de beraber kullanımı uygun bir diyagnostik strateji olabilir.©2006, Fırat Üniversitesi, Tıp Fakültesi
Akut Miyokard İnfarktüsünün Erken Teşhisinde Troponin T, Miyoglobin ve CK-MB'nin Yeri